2017
DOI: 10.1039/c7ra02464a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fiber on the antioxidant capacity, immune status, and antioxidant-relative signaling molecular gene expression in rat organs

Abstract: This study was conducted to evaluate the effects of different fibers, such as dietary pea, sweet potato, and wheat bran fibers, on the antioxidant capacity, immune status, and antioxidant-related signaling molecules of rat organs. In a 30 day experiment, a total of 44 rats were randomly divided into four dietary groups. These rats were fed either with a control diet or three basal diets supplemented with 15% pea fiber, 15% sweet potato fiber, and 15% wheat bran fiber. Results are as follows: (1) different fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…The quality of the total RNA was evaluated through agarose gel electrophoresis (1%). The total RNA purity of the spleen samples was assessed through spectrophotometric analysis at 260 and 280 nm according to a previous method ( Fang et al., 2017 ). The absorption ratios (260/280 nm) were between 1.8 and 2.0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of the total RNA was evaluated through agarose gel electrophoresis (1%). The total RNA purity of the spleen samples was assessed through spectrophotometric analysis at 260 and 280 nm according to a previous method ( Fang et al., 2017 ). The absorption ratios (260/280 nm) were between 1.8 and 2.0.…”
Section: Methodsmentioning
confidence: 99%
“…Amplification was completed with a total volume of 8 μL, which included cDNA (0.8 μL), primer pairs (1.6 μL), SYBR Premix Ex Taq_II (4 μL) (Takara, Dalian, China), and ddH 2 O (1.6 μL). The PCR procedure was in accordance with a previous study ( Fang et al., 2017 ). The expression results were assayed by using the method described by Livak and Schmittgen (2001) .…”
Section: Methodsmentioning
confidence: 99%
“…Catalase and T-SOD are the 2 primary enzymes of the enzymatic components that exhibit catalytic activity with oxygen radicals. Catalase is an important endogenous antioxidant enzyme that can eliminate organic OH − and decompose H 2 O 2 into O 2 and H 2 O ( Fang et al., 2017 ). Superoxide dismutase can collaboratively convert superoxide anions into H 2 O and O 2 ( Cao et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [42] has shown that wheat bran phenolic compounds, such as feruloylated oligosaccharides, guard human erythrocytes against oxidative damage induced by the free radicals. Another study [43] investigated the impact of supplemental wheat bran fibers on the antioxidant capacity and the antioxidantassociated signaling molecules of rat organs. They analyzed the free radical-scavenging competence against O 2 − and OH − radicals and activities of enzymatic and non-enzymatic (glutathione (GSH)) antioxidant capacities.…”
Section: Wheat Bran Compositionmentioning
confidence: 99%